Chronicles of Change: Thalassaemia Prevention Across Time - Krishnapradeep S.; Mudiyanse RM (Medical Research and Its Applications Vol. 6, 2024)
Strategies for thalassaemia prevention have evolved significantly over time. Initially, they involved methods such as identifying thalassaemia during pregnancy and opting for termination in affected cases, conducting screenings before marriage, and employing pre-implantation genetic diagnosis alongside in vitro fertilization. However, recent advances, like gene therapy, have transformed the landscape of thalassaemia management. Gene therapy, rapidly evolving, targets a wide range of medical conditions, utilizing various vectors—both viral and non-viral—for gene delivery. Promising developments on the horizon include techniques like sperm immobilization, offering researchers the chance to explore ways of identifying and selectively immobilizing defective genes in easily accessible sperm samples. Yet, this task is complex due to the inactive nature of genes in sperm, necessitating the development of genetic probes for defective gene identification. As research progresses in these areas, it becomes crucial to comprehend the pros and cons of each approach. Therefore, a comprehensive approach is vital for effective thalassaemia prevention.